Graphical password scheme to diminish shoulder surfing - Sri Ram Varma, D.; Meghana, K.; Sai Deepak, V.; Murugan, R. (International Journal of Engineering and Technology, 2017)
Many authentication schemes are known to us but none of them are completely secure. Textual password is the most common technique used by majority of the people in the industry. But Textual passwords are vulnerable to dictionary attacks, keyloggers, brute-force attacks, even guessing may work out sometimes. Alternative authentication schemes have been proposed to overcome this problem, some of them are Biometric authentication, retina based authentication, graphical password scheme ETC., Authentication Schemes such as biometric and retina scans are too costly, so they are not always preferred. Not every graphical authentication is secure and efficient. In this paper, an authentication scheme with a combination of text and colour is proposed. This allows the user to log-in to the framework a little more secure.